Requalificação do Edifício Tartaruga: proposta de hospedagem social no Centro Antigo de Manaus - Beleza, Aline Ariele da Silva (Brasil, 2024)
This Final Undergraduate Work has as its goal the study of the Tartaruga Building, a patrimony built in Manaus Historical Site. At this moment, it is in advanced deterioration level. The building is located in the cultural circuit that encompasses Adolpho Lisboa Municipal Market and Manaus Port’s Architectural and Landscaping Complex and from its history it shows its notorious values and significance for the local population. Thus, a restoration proposal for the Tartaruga Building is elaborated that embraces insertion context, relation with the surroundings and a new use based on the concept of social accommodation as adaptation to the necessities of the old city center. The development of the proposal required revision of the main restoration theories and patrimonial letters, as well as the knowledge of the property and evaluation of the conservation state.